Pengaruh tax equity terhadap tax compliance melalui trust in government - Viona Margaretha; Friska Olivia Chandra; Meco Sitardja (Penerbit Goodwood, 2020)
Purpose: This research aims to examine the effect of tax equity on tax compliance through trust in government. Research methodology: 102 respondents of Podomoro University students and Central Park Mall Visitors with purposive sampling and SEM-PLS method.. Results: This result indicate that tax equity have a positive effect on trust in government and tax compliance. Last, trust in government have a positive effect on tax compliance. Limitations: This research was only assessed based on personal taxpayer’ perspectives. Contribution: This research shows level of taxpayer’ trust become main indicator for tax compliance. Keywords: Tax awareness, Tax identity, Exchange fairness, Trust in government, Tax compliance